2016
DOI: 10.1155/2016/5460302
|View full text |Cite
|
Sign up to set email alerts
|

Natural Compounds as Regulators of NLRP3 Inflammasome-Mediated IL-1βProduction

Abstract: IL-1β is one of the main proinflammatory cytokines that regulates a broad range of immune responses and also participates in several physiological processes. The canonical production of IL-1β requires multiprotein complexes called inflammasomes. One of the most intensively studied inflammasome complexes is the NLRP3 inflammasome. Its activation requires two signals: one signal “primes” the cells and induces the expression of NLRP3 and pro-IL-1β, while the other signal leads to the assembly and activation of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
75
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(76 citation statements)
references
References 128 publications
1
75
0
Order By: Relevance
“…In support of this, a similar suggestive observation was made with the monoflavonoid quercetin ( 23 ), which was recently confirmed as a direct inhibitor of the NLRP3 inflammasome activation via interference with the oligomerization of the adaptor protein apoptosis-associated speck-like protein containing a CARD ( 70 ). Phytochemicals, such as flavonoids, are typically effective in diseases where IL-1β production and NLRP3 inflammasome activation make part of the pathophysiology, and growing evidence support the action of these compounds on NLRP3 activation ( 71 ). Thus, biflavonoids/monoflavonoids could represent a novel class of small molecule NLRP3 inflammasome inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…In support of this, a similar suggestive observation was made with the monoflavonoid quercetin ( 23 ), which was recently confirmed as a direct inhibitor of the NLRP3 inflammasome activation via interference with the oligomerization of the adaptor protein apoptosis-associated speck-like protein containing a CARD ( 70 ). Phytochemicals, such as flavonoids, are typically effective in diseases where IL-1β production and NLRP3 inflammasome activation make part of the pathophysiology, and growing evidence support the action of these compounds on NLRP3 activation ( 71 ). Thus, biflavonoids/monoflavonoids could represent a novel class of small molecule NLRP3 inflammasome inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…Antioxidants are known to impact the NLRP inflammasome. 49,50 Of special interest were extracts of L. erythrorhizon roots, H. pluvialis algae, C. sinensis leaf and Glycyrrhiza glabra root which are known to show anti-inflammatory effects on skin or skin cells. [51][52][53][54] All four antioxidants are commercially available as oil-soluble extracts and were blended to provide a fully soluble and Citrus sinensis fruit was examined using both UV and ATP activation, Figures 8 and 9.…”
Section: Treatment With Oil-soluble Antioxidantbased Blend With Uvb Amentioning
confidence: 99%
“…Latz, Xiao, and Stutz () reported that NLRP3 inflammasome not only activated the secretion of IL‐1β, but also promoted recruitment of other immune cells. Upon activation by various types of endogenous or exogenous stimuli, NLRP3 inflammasome leads to cleavage of pro‐caspase‐1 into the active form, which subsequently promotes the release of mature IL‐β (Abderrazak et al, ; Latz et al, ; Tőzsér & Benkő, ). During the development of RR, adverse stimuli might stimulate the polarization of M1 macrophages and their IL‐1β production by activating NLRP3 inflammasome.…”
Section: Introductionmentioning
confidence: 99%